Coronary Calcium Scoring and Cardiovascular Risk in Patients with Type 2 Diabetes Mellitus - Belkis Mercedes Vicente Sánchez; Gisela Zerquera Trujillo; Felix R. Jorrín Román; Lázaro E. de la Cruz Avilez; Elodia M. Rivas Alpízar (Medisur)
Background: Diabetes mellitus is considered as an independent cardiovascular risk factor. Coronary calcium scoring has proved to be a useful tool for stratifying cardiovascular risk. Objective: To quantify coronary calcium in patients with diabetes mellitus type 2 in order to estimate cardiovascular risk. Methods: A descriptive observational study was conducted. The sample included 33 patients with type 2 diabetes mellitus admitted in the Center for Diabetes Care and Education of Cienfuegos from April to July 2009. Variables studied: age, sex, nutritional assessment, illness duration, history of hypertension, hyperlipidemia and smoking. Coronary calcium was determined with multislice helical CT scanner. Results: females were predominant. Most patients were between 41 and 70 years old. More than half were from 2 to 11 years of evolution and had fasting glucose levels higher than 7.0 mmol / L. In 40.0% of diabetic patients three or more risk factors and average and high coronary calcium values were present. Out of the total, 21.7% (5 patients) has less than three risk factors and average and high values. Conclusions: Performing coronary calcium quantification can reclassify cardiovascular risk in a high percentage of estimated cases.